Beta-(1,3/1,6)-D-glucan from Pleurotus ostreatus in the prevention of recurrent respiratory tract infections: An international, multicentre, open-label, prospective study - Rennerova, Zuzana; Picó Sirvent, Leandro; Carvajal Roca, Eva; Paśnik, Jarosław; Logar, Mateja; Milošević, Katarina; Majtan, Juraj; Jesenak, Milos (Frontiers in Pediatrics, 2022)
Preschool children are particularly susceptible to recurrent upper and lower respiratory tract infections due to their immune immaturity and other contributing factors. Preventing and/or treating children suffering from recurrent respiratory tract infections (RRTIs) is challenging, and it is important to provide more clinical evidence about the safety and efficacy of natural immunomodulating preparations, including β-glucans. The aim of the present study was to assess the incidence of respiratory tract infections (RTIs) in children with a history of RRTIs for a period of 6 months (3 months of pleuran supplementation and 3 months of follow-up) compared with the same period from October to March of the previous year prior to enrolment in the study. A total of 1030 children with a mean age of 3.49 ± 1.91 years from seven countries were included in this study. The total number of RTIs observed during the study period was significantly lower compared to the same period of the previous year (7.07 ± 2.89 vs. 3.87 ± 3.19; p < 0.001). Analysis of each type of RTI revealed significant reductions in the mean number and duration of infections for all RTI subtypes compared to the previous year. This study also confirmed the beneficial safety profile of pleuran supplementation. In conclusion, pleuran supplementation represents an interesting and prospective supplement in preventing respiratory infections and reveals new strategies for supporting immune functions in the paediatric population.